The Determinants of Employee Performance in Public Sector Organizations: The Role of Work Environment and Motivation - Fahmi Rhomadhon; Zainiyatul Afifah (Eco-Entrepreneur, 2026)
Purpose: This study examines the partial and simultaneous effects of work environment and work motivation on employee performance at the Civil Service Police Unit (Satpol PP) of Bangkalan Regency.Design/Methodology/Approach: This study employs a quantitative correlational approach. Data were collected through a Likert-scale questionnaire distributed to 48 employees of the public order and community tranquility division using purposive sampling. The data were analyzed using multiple linear regression with SPSS.Findings: The results indicate that the work environment has no significant effect on employee performance, whereas work motivation has a significant positive effect. Simultaneously, work environment and work motivation significantly influence employee performance, explaining 45.2% of its variance. These findings suggest that intrinsic motivational factors play a more critical role than physical workplace conditions in determining employee performance within public-sector enforcement institutions.Research Limitations/Implications: This study is limited to a single public-sector institution and a relatively small sample size, restricting the generalizability of the findings. Future studies should include broader samples and additional variables, such as leadership style, organizational commitment, and job satisfaction.Practical Implications: Public-sector managers and policymakers should prioritize strategies that strengthen employee motivation through recognition systems, equitable incentives, and career development opportunities to improve organizational performance.Social Implications: Enhanced employee performance in public order institutions may contribute to better public service delivery and increased public trust in local government institutions.Originality/Value: This study contributes to public-sector management literature by demonstrating that intrinsic motivational mechanisms outweigh physical work-environment factors in shaping employee performance within public order enforcement organizations.